Omega-3 fatty acids and blood pressure - Mori, T. A. (Cellular and Molecular Biology, 2010)
There is substantial evidence that omega-3 fatty acids reduce blood pressure, with a greater effect in hypertensive patients and those with high-normal blood pressure. The dose of omega-3 fatty acids required to achieve a blood pressure reduction is likely to be at least 3-4 g/day. However, the magnitude of the blood pressure change can be increased by salt restriction or when omega-3 fatty acids are incorporated into a weight reducing program. It is also highly plausible that increased omega-3 fatty acid consumption as part of a dietary change including increased consumption of fruits and vegetables, and moderation of salt intake, will confer significant cardiovascular benefit